Near-infrared luminescence and energy transfer mechanism in K2YF5:Nd3+, Yb3+. (February 2019) - Bian, Xiaomin; Shi, Qiufeng; Cui, Cai'e; Wang, Lei; Tian, Yue; Xu, Bing; Mamytbekov, Zhailoo K.; Huang, Ping
Graphical abstract: The rising time of Nd 3+ 4 F3/2 state luminescence dependence on Yb 3+ concentration reveals the first step cross relaxation energy transfer from Nd 3+ ( 4 G9/2 → 4 F3/2 ) to Yb 3+ ( 2 F7/2 → 2 F5/2 ). Highlights: The first step energy transfer was first revealed by Yb 3+ content dependence of rising time of Nd 3+ 4 F3/2 luminescence. The second step energy transfer efficiency from Nd 3+ 4 F3/2 to Yb 3+ is up to 89% in K2 YF5 :1.0%Nd 3+, 8.0%Yb 3+ . The electric dipole-dipole interaction mechanism responsible for the second step energy transfer was confirmed. Abstract: A series of crystalline powder samples of K2 YF5 :1.0%Nd 3+, x%Yb 3+ (x = 0, 2.0, 5.0 and 8.0) were prepared by hydrothermal synthesis method. The excitation and emission spectra and luminescence decay curves were studied. The decay time of Nd 3+ 4 D3/2 and 2 P3/2 independence on Yb 3+ concentration illustrates the absence of direct cross relaxation energy transfer from these two states to Yb 3+ in K2 YF5 . However, the shortening of rising time of Nd 3+ 4 F3/2 luminescence with Yb 3+ concentration reveals the existence of cross relaxation energy transfer from Nd 3+ to Yb 3+, the potential energy transfer process from Nd 3+ ( 4 G9/2 → 4 F3/2 ) to Yb 3+ ( 2 F7/2 → 2 F5/2 ) has been proposed. Furthermore, the second step energy transfer from Nd 3+ ( 4 F3/2 → 4 I9/2 ) to Yb 3+ ( 2 F7/2 → 2 F5/2 ) has been verified and the transfer efficiency of 89% from Nd 3+ 4 F3/2 state to Yb 3+ has been obtained in K2 YF5 :1.0%Nd 3+, 8.0%Yb 3+ . The mechanism responsible for the efficient energy transfer is electric dipole-dipole interaction.